Serotonin syndrome: pills, thrills and shoulder aches - Proudfoot, Malcolm (BMJ Publishing Group, 2013)
This case demonstrates an acute presentation of unwitnessed seizure causing typical injuries. Progress in hospital was complicated by worsening autonomic disturbance and agitation, typical for serotonin syndrome, suspected in light of recent selective serotonin reuptake inhibitor  antidepressant initiation. Supportive care required treatment in the intensive care unit setting but full recovery ensued. This case not only reminds clinicians of the potential pitfalls in assessing postictal injured patients, but also that serotonin syndrome requires a high-index of diagnostic suspicion given the range of presenting features. Management ranges from simple withdrawal of the offending agent to specific therapies such as a cyproheptadine.